FRI0325 Clinical and Serological Features According To Age at Diagnosis of Primary Sjögren's Syndrome. (15th July 2016) - Bohόrquez Heras, C.; Sanchez-Piedra, C.; Fernandez Castro, M.; Andreu, J.L.; Martinez Taboada, V.; Olivé, A.; Rosas, J.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a chronic systemic autoimmune disease that usually affects middle age women. It is characterized mainly by the involvement of the exocrine glands; However, patients with pSS presents a broad spectrum of systemic involvement and serologic characteristics. Objectives: The aim of this study is to analyze clinical and serological differences in different age at diagnosis groups in a pSS Spanish cohort. Methods: This is a multicenter transversal study of pSS patients whose fulfilled European-American consensus criteria from thirty-three Rheumatology Units. The patients were randomized into the following age groups: <35 years, 35–50 years, 50–65 years and>65 years. Epidemiological, clinical and serological data were collected. All patients signed an informed consent, and the study was approved by the local ethics committees. Qualitative data were compared using the Chi-square tests. Quantitative variables were analyzed with a Kruskal-Wallis test. A value of p<0.05 was considered as significant. Results: Four hundred and thirty-seven patients were included. The median age of the cohort was 58 years. Ninety-five percent of them were women.There were no statistically significant differences in the men and women percentage.The disease symptoms were initiated more frequently in 35–50 years group (38.5%).There were no statistically significant differences in the time to disease progression in the four age at diagnosis groups. No statistically significant differences were found in sicca syndrome among age groups. Ocular and oral symptoms were present in 95% of patients. The glandular involvement (46.7%), central nervous system (14.13%) and Raynaud's phenomenon (29.3%) showed significantly more often in patients under 35 years. Genital involvement (54.5%) and asthenia (72.4%) showed significantly more often in the group of 35–50 years. The gastrointestinal involvement (20%) occurred significantly more frequently in the group of 50–65 years. Splenomegaly and cardiac involvement were less frequent manifestations in all four groups of patients (<4%). Rheumatoid factor (RF) positive was significantly higher in those under 35 years (77.1%). The anti-anti-SSA and SSB antibodies tended to be more frequently positive in groups <35 years (96.7% and 79.3% respectively) and>65 years (100% and 75% respectively). There were no significant differences in the ANA, anti-DNA, anti-Sm, anti-RNP, cryoglobulins and antiphospholipid antibodies values between groups. Conclusions: Patients under 65 years old have an increased degree of systemic involvement. There are no differences in the presence of sicca syndrome. The FR is significantly more common in patients younger than 35-year-old, while the anti-Ro and anti-La antibodies tend to be it in more extreme age groups. Disclosure of Interest: None declared